The Compliance with Blood Adding Tablet Consumption Based on Theory of Planned Behavior - Bahtiar, Harismawati; Yusriani, Yusriani; Idris, Fairus Prihatin (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: In Indonesia, 23.9% of adolescent women between the ages of 15 and 24 suffer from anemia. Anemia occurs at all phases of human development and is more prevalent in young women, including female students. Compliance with iron supplement consumption is a form of behavior used to prevent and treat anemia, so the tendency of young women to adhere to regular iron supplement consumption can be analyzed using the Theory of Planned Behavior.Purpose: Understanding the relationship and influence of attitudes, subjective norms, intentions, and behavioral control on female students at Al-Ikhlas Islamic Boarding School Ujung Bone's adherence to the consumption of blood-supplemented tablets to prevent anemia in 2023.Methods: A quantitative investigation employing a cross-sectional design. Chi-square is the statistical test that is used. The research instrument was a structured questionnaire form, and 120 female students served as the sample.Results: At Al-Ikhlas Islamic Boarding School Ujung Bone in 2023, there is a statistically significant relationship between attitudes, subjective norms, intentions, and behavioral control and adherence to blood-added tablet consumption.Conclusion: The majority of female pupils who adhere to the consumption of iron tablets demonstrate obedient behavior. Researchers propose that KIE can enhance the knowledge of female students. The puskesmas can provide additional health education regarding the adverse effects female students experience after taking iron tablets. Future researchers can use mixed methods by conducting FGDs with female students, instructors, and program implementers. In addition, assess Hb levels to determine the effect of taking iron tablets.